1991
DOI: 10.1111/j.1540-8183.1991.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Balloon Inflation Duration on the Acute Angiographic Result of Percutaneous Transluminal Coronary Angioplasty

Abstract: This study was performed to evaluate the importance of the duration of balloon inflation during PTCA, by comparing two common inflation durations. Patients were randomized to a 30-second inflation protocol (group I, 83 procedures, 109 lesions), or a 60-second protocol (group II, 83 procedures, 115 lesions). There were no differences in baseline characteristics between the two groups, and no subsequent differences in mean inflation number (3.4 +/- 1.6 vs 3.1 +/- 1.6), residual stenosis (34% +/- 17% vs 33% +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…When angioplasty was first introduced in the last twentieth century, early randomized trials revealed immediate benefit of prolonged balloon inflation, although the sustainability of the patency benefit is conflicting [810]. However, the immediate benefit of prolonged angioplasty has not been consistently reported in randomized trials [11].…”
Section: Introductionmentioning
confidence: 99%
“…When angioplasty was first introduced in the last twentieth century, early randomized trials revealed immediate benefit of prolonged balloon inflation, although the sustainability of the patency benefit is conflicting [810]. However, the immediate benefit of prolonged angioplasty has not been consistently reported in randomized trials [11].…”
Section: Introductionmentioning
confidence: 99%